Thermal and Economic Analysis of Gas Turbine Using Inlet Air Cooling System - Ibrahim, Thamir K.; Awad, Omar I.; M. Kh., Abdolbaqi (2016)
A basic goal of operation management is to successfully complete the life cycle of power systems, with optimum output against minimal input. This document intends calculating both, the performance and the life cycle cost of a gas turbine fitted with an inlet air cooling mechanism. Correspondingly, both a thermodynamic and an economic model are drawn up, to present options towards computing the cooling loads and the life cycle costs. The primary observations indicate that around 120MWh of power is derived from gas turbine power plants incorporating the cooling mechanism, compared to 96.6 MWh for units without the mechanism, while the life cycle cost is lower for units incorporating the cooling process. This indicates benefits in having the mechanism incorporated in the architecture of a gas turbine.